Estimating North Korean GNP by Physical Indicators Method - Chun, Hong Tack (Korea Development Institute, 1992)
This paper is organized as follows. In section Ⅱ, the literature on North Korean GNP is reviewed with emphasis on the estimation method. Section Ⅲ attempts to estimate per capita GNP of North Korea using the physical indicators method. In the last section, we try to assess the plausibility of the resulting estimates along with other well-known estimates. (※서문에서 발췌한 내용임)